Customer Service Management on Enhancing Customer Loyalty in Food and Beverage Industry: Case Study of Starbucks Malaysia - Darren Chan, Chee Shern; Tio, Fang Kee; Chua, Siew Woon; Soon, Shi Wen; Pok, Wei Lun; Mohammad, Farajnezhad (INTI International University, 2024)
In the highly competitive coffee industry, the operation of a successful coffee shop involves more than just providing a simple cup of coffee. Organizations are now recognizing the need to focus on delivering high-quality service to gain a competitive advantage. Emphasizing service quality is crucial for building customer loyalty. This paper aims to demonstrate and investigate the service quality using the SERVQUAL model, specifically in the context of Malaysia's Starbucks outlets. To gather real-time data, this paper employs a questionnaire-based survey. A total of 221 questionnaires were distributed to the public. Following data collection, the obtained data is analyzed using SPSS software. Additionally, this paper offers insights into the current state of Starbucks in Malaysia and proposes practical actions to enhance service quality. The objective is to not only attract and retain customers but also cultivating customer loyalty within the competitive coffee chain industry. By focusing on the SERVQUAL model, this research seeks to identify the key dimensions of service quality that significantly impact customer loyalty. These insights are essential for Starbucks to make informed decisions and implement effective strategies to elevate its service quality.